A new view into political business cycles: Household expenditures in Albania - Holger Kächelein; Drini Imami; Endrit Lami (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2008)
Over the last decades, there has been plenty of research and articles on Political Business Cycles (PBC), aiming at analyzing and explaining the use of fiscal and monetary instruments to stimulate economic growth before elections, to impress the voters. Following other researches for PBC in Albania, in which there was found clear evidence of fiscal expansion before elections, but no significant changes in inflation and GDP, as theory predicts, we analyze the peoples' expectations related to elections outcomes, and the way these expectations influence their decisions to spend, and consequently the macroeconomic variables.
Keywords: E32; O23; N14; 330; Political Business Cycle; Household Behaviour; Albanian; Politischer Konjunkturzyklus; Wahlverhalten; Konsumentenverhalten; Privater Haushalt; Albanien